THE RELATIONSHIP OF THE ROLE OF THE FAMILY AND LABOR DECISION MAKING IN PREGNANT WOMEN IN THE III TRIMESTER IN THE INDEPENDENT PRACTICE OF MIDWIFERES IN ENDANG BANTEN FOR THE PERIOD OF NOVEMBER-DECEMBER 2023 - Rindiyanti, Endang; Sutarno, Maryati (HEARTY, 2025)
Background: WHO in 2020 reported that the maternal mortality rate in the world was 287 per 100,000 live births. In developing countries 27.1% and in developed countries 16.3% of the highest maternal deaths are caused by bleeding caused by the selection of birth attendants. One of the Efforts to reduce MMR is decision making is a fundamental ability for health practitioners, in particular in midwifery care. Research Objectives: To know connection role family with decision making delivery in third trimester pregnant women at the Mandiri Midwife Practice in Endang. Research Method: analytical survey with the type of research cross-sectional. some pregnant women who carry out pregnancy checks at T PMB Endang in November 2023 there will be 97 people . The sampling technique uses purposive sampling technique. Research Results: majority of respondents own role family Good that is as many as 46 (94%) and respondents with category decision appropriate namely 45 respondents (92%) so there is a significant relationship between Family Roles With Maternity Decision Making in Third Trimester Pregnant Women obtained p value 0.000 (P < 0.05). Conclusions and Suggestions: There is a significant relationship between Family Role Relationships With Maternity Decision Making in Third Trimester Pregnant Women. It is hoped that midwives will provide evaluations for health workers to better understand the emotional conditions of pregnant women when making decisions.